The Wage Penalty of Dialect-Speaking - Yuxin Yao; Jan C. van Ours (Institute for the Study of Labor (IZA), 2016)
Our paper studies the effects of dialect-speaking on job characteristics of Dutch workers, in particular on their hourly wages. The unconditional difference in median hourly wages between standard Dutch speakers and dialect speakers is about 10.6% for males and 6.7% for females. If we take into account differences in personal characteristics and province fixed effects male dialect speakers earn 4.1% less while for females this is 2.8%. Using the geographic distance to Amsterdam as an instrumental variable to dialect-speaking, we find that male workers who speak a dialect earn 11.6% less while for female workers this is 1.6%. Our main conclusion is that for male workers there is a significant wage penalty of dialect-speaking while for female workers there is no significant difference.
Keywords: J24; I2; 330; dialect-speaking; wage penalty; job characteristics